Incidence and management of sucking pest complex in dual toxin transgenic Bt cotton hybrids - Kumar, B Dileep; Sridevi, G; Babu, T Ramesh (Indian Journal of Plant Protection, 2020)
The performance of dual toxin transgenic Bt cotton hybrids viz., Bunny, Mallika, Neeraja, Brahma, Tulasi-9, RCH-2, RCH-530 and a non-Bt hybrid, Orugallu Krishna (WGHH-2) against insect pests of cotton was undertaken during Kharif 2011 and 2012 at Regional Agricultural Research Station, Warangal. The population (pooled mean for both the years) of aphids and whiteﬂies showed no signifcant variation among the various BG-II/non-Bt hybrids under protected conditions. The population ranged between 3.8 - 5.3 and 1.5 - 2.0/top 3 leaves in aphids and whiteﬂies, respectively. However, leafhoppers and thrips varied signifcantly amongst the various BG-II/nonBt hybrids. The population of leafhoppers was signifcantly lowest in non-Bt Orugallu Krishna (1.5 leafhoppers/top 3 leaves) and was on par with only Neeraja (1.6 leafhoppers/top 3 leaves). The population ranged between 1.8 and 3.2 leafhoppers/top 3 leaves in the remaining hybrids, the highest (3.2 leafhoppers/top 3 leaves) being in RCH-2. The population of thrips ranged between 9.7 and 17.8 thrips/top 3 leaves. A total of six need based sprayings were required for dual toxin Bt hybrids to manage the sucking pest complex in both Kharif, 2011 and 2012. During both the years the cost-beneft ratio was found to be higher in RCH-530.